Enhanced antibacterial effects of green synthesized ZnO NPs using Aristolochia indica against Multi-drug resistant bacterial pathogens from Diabetic Foot Ulcer - Katherin Steffy; Ganesan Shanthi; Anson S. Maroky; Sachidanandan Selvakumar (Elsevier, 2018)
Background: Increased incidence of Multi-drug resistance in microorganisms has become the greatest challenge in the treatment of Diabetic Foot Ulcer (DFU) and urges the need of a new antimicrobial agent. In this study, we determined the bactericidal effects of ZnO nanoparticles (ZnO NPs) green synthesized from Aristolochia indica against Multi-drug Resistant Organisms (MDROs) isolated from pus samples of DFU patients attending in a tertiary care hospital in South India. Methods: ZnO NPs were characterized by UV-vis-DRS spectroscopy, Atomic Force Microscopy (AFM), Transmission Electron Microscopy (TEM) and for its zeta potential value. MIC/MBC assays were performed to determine bactericidal or bacteriostatic effects. Time-kill assays, Protein leakage and Flow cytometric analysis evaluated bacterial cell death at 1x MIC and 2x MIC concentrations of ZnO NPs. Results: ZnO NPs of size 22.5 nm with a zeta potential of −21.9 ± 1 mV exhibited remarkable bactericidal activity with MIC/MBC ranging from 25 to 400 μg/ml with a significant reduction in viable count from 2 h onwards. Protein leakage and Flow cytometric analysis confirmed bacterial cell death due to ZnO NPs. Conclusion: This study concluded that green synthesis protocol offers reliable, eco-friendly approach towards the development of antimicrobial ZnO NPs to combat antibiotic drug resistance. Keywords: Aristolochia indica, ZnO NPs, Time-kill kinetics, Protein leakage analysis, Flow cytometry